Biodegradable Dual Semicircular Patch Antenna Tile for Smart Floors - Khalili, Hossein Fazeli; et al. (IEEE Antennas and Wireless Propagation Letters, 2019)
A dual semicircular microstrip patch antenna implemented on a biodegradable substrate is presented for operation in the [863-873] MHz and [2.4-2.5] GHz frequency bands. To cover these frequency bands, two semicircular patches are compactly integrated onto a biodegradable cork tile, commonly found as support in laminate flooring, serving as a substrate. Thereby, the antenna tile may be seamlessly embedded as a sublayer of the floor structure. A higher-order mode is generated by applying via pins in the antenna topology to produce a conical radiation pattern with a null at broadside and sectoral coverage in the vertical plane. As such, the concealed floor antenna covers all azimuth angles of arrival in smart houses. The antenna performance is fully validated, also when the tile is covered by different polyvinyl chloride sheets. Owing to the supplementary design margins, the antenna impedance bandwidth remains covered. Moreover, the radiation patterns are measured in various elevation planes. Under stand-alone conditions, a radiation efficiency and a maximum gain of 74.3% and 5.8 dBi at 2.45 GHz and 48.1% and 2 dBi at 868 MHz are, respectively, obtained. Its omnidirectional coverage in the horizontal plane, stable performance on the inhomogeneous and biocompatible cork substrate and for various inhomogeneous superstrates, and its low-profile integration make the proposed antenna an excellent candidate for smart floors and smart houses.
Created from Fastlane, Scopus look-up
Keywords: Antenna tile; biodegradable cork; dual-band microstrip antenna; Internet of Things (IoT); smart floors